Outlines - Any Hopkins (Longman, 1990)
This book includes the following special features: Astimulating selection of text types and written styles, including postcards and small ads, instructions, persuasive writing, narrative and composition. Practice in writing skills relevant immediate needs as well as groundwork for higher level writing. Discussion and analysis activities in each unit, leading to follow-up writing tasks. An extensive key, including model texts, which enables students to systematically analyse, assess and improve their own writing